Cultivando e aprendendo - Araújo, Jucelio Alexandre de; Almeida, Gisele Rodrigues de; Gonçalves, Jesuína Aparecida; Bordinhão, Andréa Chiozini (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
VER PDF